Tests of glass fibre reinforced polymer rectangular concrete columns subjected to concentric and eccentric axial loading. (15th November 2017) - Elchalakani, Mohamed; Ma, Guowei
Highlights: New tests on steel and GFRP RC columns were performed. GFRP RC columns can achieve greater strain and deformation ductility than steel RC columns. The average axial load carrying capacity of GFRP RC columns was 93.5% of their steel RC column counterparts. GFRP RC columns exhibited 3.2% average increase in the load carrying capacity. The steel RC columns achieved an average enhancement of 15.8%. Abstract: The use of Glass Fibre-Reinforced Polymer (GFRP) reinforcement as an alternative to steel for use in Reinforced Concrete (RC) structures has developed significantly in recent years. GFRP's excellent corrosion resistance, high tensile-strength-to-weight ratio, non-magnetic, nonconductive make it an excellent solution for projects requiring improved corrosion resistance or reduced maintenance costs. Despite a number of recent studies illustrating the effective use of GFRP rebars as longitudinal reinforcement for concrete compression members, the current international design codes such as ACI 440.1R-15, CAN/CSA S806, TR55, ISO 10406-1, and fib do not recommend including GFRP reinforcement in the compression member capacity calculations. The experimental study detailed in this paper involved construction and testing of 17 rectangular concrete columns reinforced with both steel and GFRP rebars. The columns were tested to failure under various loading conditions, in order to determine the effect of load eccentricity on axial capacity. The effect of ligature spacing and confinement area on axial capacity and ductility were also examined. The most important finding is that GFRP RC columns utilising less concrete cover can achieve greater strain and deformation ductility than equivalent steel RC columns. It was shown that the load carrying capacity and ductility of GFRP reinforced columns increased when the ligature spacing was reduced from 150 mm to 75 mm. It was also found that, the average axial load carrying capacity of GFRP RC columns was 93.5% of their steel RC column counterparts. It was also found that, the GFRP RC columns under concentric load exhibited 3.2% average increase in the load carrying capacity with respect to the plain concrete section capacity, whereas the steel ones achieved an average enhancement of 15.8%.